Niedobory konsumpcji w gospodarstwach domowych z dziećmi z niepełnosprawnością - Janoś-Kresło, Mirosława (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Not every household can afford, mainly due to limited financial resources, to meet their needs in a satisfactory manner. The aim of the article is to present selected findings of empirical research (qualitative study — FGI, IDI and quantitative study — CAPI and CAWI, requested by the respondent) carried out for the needs of the project Entrepreneurial and Consumer Behaviour of Families Caring for Children and Youth with Disabilities. The article presents the financial situation of households with a child/children with disabilities, the financial obligations and purposes of consumer credits and loans, the most acute shortages in the household, the allocation of additional income and the ways of coping with difficulties
Keywords: consumption; shortages; households; children with disabilities